A History of the French Working Class. Vol. I/ The Age of Artisan Revolution 1815-1871, vol. II/Workers and the Bourgeois Republic 1871-1839 - Simoni, Pierre (Labour / Le Travail, 1996)
The article reviews the books "A History of the French Working Class: The Age of Artisan Revolution 1815-1871," and "A History of the French Working Class: Workers and the Bourgeois Republic 1871-1839," by Roger Magraw.
Keywords: BOOKS -- Reviews; HISTORY of the French Working Class: The Age of Artisan Revolution 1815-1871, A (Book); HISTORY of the French Working Class: Workers & the Bourgeois Republic 1871-1939, A (Book); MAGRAW, Roger; Nonfiction